# General and Middle Term

The Binomial theorem formula helps us to find the power of a binomial without having to go through the tedious process of multiplying it. Further use of the formula helps us determine the general and middle term in the expansion of the algebraic expression too. In this article, we will look at some simple ways to find the middle term and general term when a binomial $$(a + b)^n$$ is expanded using the binomial theorem.

## Binomial Theorem Formula – General Term

(Source: Pixabay)

By the Binomial theorem formula, we know that there are (n + 1) terms in the expansion ofÂ $$(a + b)^n$$. Now, let’s say that $$T_1$$,Â $$T_2$$,Â $$T_3$$,Â $$T_4$$, …Â $$T_{n + 1}$$ are the first, second, third, fourth, … (n + 1)th terms, respectively in the expansion ofÂ $$(a + b)^n$$. Therefore,

$$T_1$$ =Â $${n} \choose {0}$$$$a^n$$
$$T_2$$ =Â $${n} \choose {1}$$$$a^{n – 1}$$.b
$$T_3$$ =Â $${n} \choose {2}$$$$a^{n – 2}$$.$$b^2$$
$$T_4$$ =Â $${n} \choose {3}$$$$a^{n – 3}$$.$$b^3$$
…..
$$T_{n + 1}$$ =Â $${n} \choose {n}$$$$b^n$$

Generalizing it, we have the formula for the general term:

$$T_{r + 1}$$ =Â $${n} \choose {r}$$$$a^{n – r}$$$$b^r$$

where 0Â â‰¤ rÂ â‰¤ n. Let’s look at an example now.

### Example 1

Find the fourth term in the expansion ofÂ $$(3x – y)^7$$.

Solution. In this example, a = 3x, b = – y, and n = 7. From the above formula, we have
$$T_{r + 1}$$ =Â $${n} \choose {r}$$$$a^{n – r}$$$$b^r$$

To find the fourth term,Â $$T_4$$, r = 3. Therefore,
$$T_4$$ =Â $$T_{3 + 1}$$ =Â $${7} \choose {3}$$$$(3x)^{7 – 3}$$.$$(- y)^3$$
=Â $$\frac {7 . 6 . 5}{1 . 2 . 3}$$$$(81x^4)$$.$$(- y)^3$$ = – 2835$$x^4$$$$y^3$$

Hence, the fourth termÂ in the expansion ofÂ $$(3x – y)^7$$ =Â – 2835$$x^4$$$$y^3$$

Download Binomial Theorem Cheat SheetÂ by clicking on the button below

## Binomial Theorem Formula – Middle Term

When you are trying to expandÂ $$(a + b)^n$$ and ‘n’ is an even number, then (n + 1) will be an odd number. Which means that the expansion will have odd number of terms. In this case, the middle term will be the ($$\frac {n}{2}$$ + 1)th term.

For example, if you are expandingÂ $$(x + y)^2$$, then the middle term will be theÂ ($$\frac {2}{2}$$ + 1) = 2nd term. ($$\frac {n}{2}$$ + 1)th term is also denoted as ($$\frac {n + 2}{2}$$)th term.

When you are trying to expandÂ $$(a + b)^n$$ and ‘n’ is an odd number, then (n + 1) will be an even number. Hence, there are two middle terms: ($$\frac{n + 1}{2}$$)th term andÂ ($$\frac {n + 3}{2}$$)th term.

For example, if you are expandingÂ $$(x + y)^3$$, then the middle terms will be, ($$\frac {3 + 1}{2}$$) = 2nd term andÂ ($$\frac {3 + 3}{2}$$) = 3rd term. Let’s look at an example now.

### Example 2

Find the middle term/s in the expansion ofÂ ($$\frac {x}{2}$$ + 3y)9.

Solution. In this example, since n (= 9) is odd, we have two middle terms namely,
($$\frac {9 + 1}{2}$$) = 5th term andÂ ($$\frac {9 + 3}{2}$$) = 6th term.

We also have,
a =Â $$\frac {x}{2}$$, b = 3y, and n = 9.

We know that,
$$T_{r + 1}$$ =Â $${n} \choose {r}$$$$a^{n – r}$$$$b^r$$

To find the fifth term,Â $$T_5$$, r = 4. Therefore,
$$T_5$$ =Â $$T_{4 + 1}$$ =Â $${9} \choose {4}$$$$(\frac {x}{2})^{9 – 4}$$$$(3y)^4$$
=Â $$\frac {9 . 8 . 7 . 6}{1 . 2 . 3 . 4}$$($$\frac {x^5}{32}$$)($$81y^4$$) = $$\frac {5103}{16}$$$$x^5$$$$y^4$$.

Similarly,
$$T_6$$ =Â $$T_{5 + 1}$$ =Â $${9} \choose {5}$$$$(\frac {x}{2})^{9 – 5}$$$$(3y)^5$$
=Â $$\frac {9 . 8 . 7 . 6 . 5}{1 . 2 . 3 . 4 . 5}$$($$\frac {x^4}{16}$$)($$243y^5$$) = $$\frac {15309}{8}$$$$x^4$$$$y^5$$.

Therefore,Â the middle terms in the expansion ofÂ ($$\frac {x}{2}$$ + 3y)9Â areÂ $$\frac {5103}{16}$$$$x^5$$$$y^4$$ andÂ $$\frac {15309}{8}$$$$x^4$$$$y^5$$.

## More Solved Examples for You

Question 1: Find the coefficient ofÂ $$x^6$$ in the expansion ofÂ $$(x + 2)^9$$.

Answer : We know that the binomial expansion ofÂ $$(a + b)^n$$ is,
$$T_{r + 1}$$ =Â $${n} \choose {r}$$$$a^{n – r}$$$$b^r$$

Now, the (r + 1)th term in the expansion ofÂ $$(x + 2)^9$$ will be:
$$T_{r + 1}$$ =Â $${9} \choose {r}$$$$(x)^{9 – r}$$$$(2)^r$$

From the above equation, we can deduce that the coefficient of the x-term isÂ $${9} \choose {r}$$$$(2)^r$$

Next, we need to find the coefficient ofÂ $$x^6$$. Hence,
$$x^6$$ =Â $$(x)^{9 – r}$$
Or, 6 = 9 – r, therefore r = 3.

Using this value of ‘r’,
The coefficient ofÂ $$x^6$$ =Â $${9} \choose {3}$$$$(2)^3$$
=Â $$\frac {9 . 8 . 7}{1 . 2 . 3}$$.(8) = 672.

Solved Questions for You

Question 1: What is the use of Binomial theorem?

Answer: The Binomial theorem formula assists us in finding out the power of a binomial without having to go through the dreary method of multiplying it. Further, use of the formula will assist us in determining the general and middle term in the expansion of the algebraic expression too.

Question 2: What is a binomial expression?

Answer: A binomial refers to a mathematical expression that contains two terms, which we must separate through addition or subtraction. To add binomials, you need to combine like terms to get your answer. To multiply binomials, you need to make use of the distributive property. More often than not, you will not get a binomial answer with multiplication

Question 3: What is a binomial factor?

Answer: Binomial factors refer to polynomial factors that have exactly two terms. Binomial factors are easy to solve, and the roots of the binomial factors are the same as the roots of the polynomial. Thus, the first step to find the roots is to factor a polynomial.

Question 4: What is the square of a binomial?

Answer: The square of a binomial refers to the sum of the square of the first terms, twice the product of the two terms, and finally the square of the last term.

Share with friends

## Customize your course in 30 seconds

##### Which class are you in?
5th
6th
7th
8th
9th
10th
11th
12th
Get ready for all-new Live Classes!
Now learn Live with India's best teachers. Join courses with the best schedule and enjoy fun and interactive classes.
Ashhar Firdausi
IIT Roorkee
Biology
Dr. Nazma Shaik
VTU
Chemistry
Gaurav Tiwari
APJAKTU
Physics
Get Started